2012
DOI: 10.1007/s00330-012-2732-7
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the entire cerebrospinal fluid volume with a multistation 3D SPACE MR sequence: feasibility study in patients with hydrocephalus

Abstract: • MRI assessment of CSF volume is feasible in healthy volunteers/hydrocephalus patients. • CSF volume can be obtained on a whole-body scale. • The ratio of subarachnoid and ventricular CSF is constant in healthy volunteers. • CSF linear discriminant analysis can distinguish between patients and healthy volunteers. • Entire CSF volume imaging is useful for diagnosing and following hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Previous studies attempted to segment CSF in LVs using similar methodology with ours in healthy controls and MS patients . CSF in ventricles and subarachnoid space has been measured using computerized tomography in subarachnoid hemorrhage detection, T2‐weighted 3D spin echo sequences in normal pressure hydrocephalus and Alzheimer's disease, T2‐weighted sequence in traumatic brain injury, and 3D SPACE MR in hydrocephalus . Although comparing different methods of CSF segmentation is not in the scope of this study, we showed that DTI‐based wbCSF segmentation is feasible and can be used to monitor clinical symptomatology in patients with MS.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies attempted to segment CSF in LVs using similar methodology with ours in healthy controls and MS patients . CSF in ventricles and subarachnoid space has been measured using computerized tomography in subarachnoid hemorrhage detection, T2‐weighted 3D spin echo sequences in normal pressure hydrocephalus and Alzheimer's disease, T2‐weighted sequence in traumatic brain injury, and 3D SPACE MR in hydrocephalus . Although comparing different methods of CSF segmentation is not in the scope of this study, we showed that DTI‐based wbCSF segmentation is feasible and can be used to monitor clinical symptomatology in patients with MS.…”
Section: Discussionmentioning
confidence: 84%
“…11,12 With this technique, thinner section images and 3D data (by using < 1-mm 3 voxels) can be acquired with acceptable acquisition time (approximately 5 minutes), minimizing the partial volume effect between small entities and surrounding tissue. 3,12 Our previous studies demonstrated that T2W 3D-SPACE with variant flip-angle mode images may show the flow dynamics of CSF in the ventricular system.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 With the development of MRI technology, the whole cranium, including CSF-containing spaces (especially the ventricular system), and CSF circulation are better evaluated with 3D isotropic submillimetric data obtained by 3-T MR units. 3,11 By using a relatively new technique called 3D sampling perfection with application-optimized contrasts using different flip-angle evolutions (3D-SPACE) developed by Mugler et al, it has now become possible to scan the whole cranium with < 1-mm 3 voxels within an acceptable time period and without exceeding specific absorption rate limits in 3-T scanners.…”
mentioning
confidence: 99%
“…3D sequences like SPACE (Sampling Perfection with Application optimized Contrasts using different flip angle Evolution) are well established in whole body MR imaging [2] and in selected neuroradiological indications [3]. The 3D approach allows isotropic high-resolution 3D images by using a slab selective, variable excitation pulse.…”
Section: Introductionmentioning
confidence: 99%